Suitability of Egg-laying Habitat and Its Relationship with the Number of Green Turtles (Chelonia mydas) that landed on Pangumbahan Beach Sukabumi - Riska Rismawati; Diana Hernawati; Diki Muhamad Chaidir (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
During the nesting season, green turtles have an instinct to return to their original place to lay their eggs. The success of turtle egg laying is influenced by the suitability of the beach for their nesting habitat which consists of physical and biological factors. The purpose of this study was to determine the suitability of the physical and biological factors of green turtle nesting habitat and its relationship to the number of green turtles landed at each station. The research method used is observation, the observation station is determined by purposive sampling, and the data analysis technique used is quantitative. The result is that physical and biological factors consisting of beach width and slope, sand texture and temperature, and vegetation at each landing station on Pangumbahan beach are still suitable as green turtle nesting sites except station 6. There were 47 green turtles that landed, and station 2 has the highest number of turtles landing, which is 16 turtles. Meanwhile, at station 6, no turtles landed. From the results of the correlation analysis, the beach slope factor and the vegetation density factor have a very strong and significant relationship with the number of turtles that landed. As for the other factors have a fairly - strong relationship. The conclusion is that all factors, both physical and biological factors from the beach, affect the number of green turtles that land, as evidenced by the relationship between the two variables.